1984
DOI: 10.1002/jcb.240240106
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein insertion into developing photosynthetic membrane Regions of Rhodopseudomonas sphaeroides

Abstract: Previous studies have suggested that much of the B800-850 light-harvesting bacteriochlorophyll a-protein complex is inserted directly into the intracytoplasmic photosynthetic membrane of Rhodopseudomonas sphaeroides. In contrast, the B875 light-harvesting and reaction center complexes are assembled preferentially at peripheral sites of photosynthetic membrane growth initiation. The basis for this apparent site-specific polypeptide insertion was examined during the inhibition of RNA and protein syntheses. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…When liposomes prepared from native R. sphaeroides phospholipids were treated with phospholipase A2, both PE and PC were hydrolyzed to comparable extents, suggesting that the inactivity toward PC in the native membranes could be due to a lack of enzyme accessibility. PC was also refractory to phospholipase A2 digestion of the upper pigmented band, even though both sides of the bilayer are exposed in this membrane fraction (Inamine et al, 1984). These results imply that protein components of both the upper pigmented band and chromatophores somehow protect PC from digestion.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When liposomes prepared from native R. sphaeroides phospholipids were treated with phospholipase A2, both PE and PC were hydrolyzed to comparable extents, suggesting that the inactivity toward PC in the native membranes could be due to a lack of enzyme accessibility. PC was also refractory to phospholipase A2 digestion of the upper pigmented band, even though both sides of the bilayer are exposed in this membrane fraction (Inamine et al, 1984). These results imply that protein components of both the upper pigmented band and chromatophores somehow protect PC from digestion.…”
Section: Discussionmentioning
confidence: 91%
“…31P-NMR spectra revealed that after 60 min of digestion, approximately 75,60, and 25% of the PE, PC, and PG, respectively, were digested to form their corresponding lysophospholipids (not shown). Since this suggested that chromatophore proteins may be responsible for modulating the activity of phospholipase A2 toward PC, enzymatic digestion was performed on the membrane fraction isolated as an upper pigmented band, which has a protein composition largely distinct from that of chromatophores (Niederman et al, 1979) and consists of open fragments (Inamine et al, 1984). The lipid composition of the upper pigmented band was found to be 20% PC, 43% PE, and 37% PG (Table 11).…”
Section: Effect Of Phospholipase A2 Digestion On Carotenoidspectra Anmentioning
confidence: 99%
“…The LH apparatus of R. rubrum is relatively simple and comprises only one antenna complex, referred to as LH1, which surrounds the RC and consists of a ring-like array of 16 ␣␤-polypeptide subunits, each binding a pair of BChls and one Spx (8). Membrane fragments from R. rubrum S1 were prepared as described in (9). Isolated LH1 complexes devoid of RCs were obtained as described in (10).…”
Section: Methodsmentioning
confidence: 99%
“…Last but not least, we must further our understanding of the biosynthesis of the proteins and how the stoichiometry of polypeptides within and between complexes is controlled [cf. 48,491.…”
Section: :Jcb Thornber Et Atmentioning
confidence: 97%